Communication Privacy Management Of Celebgrams In Bengkulu City - Ardiyes Mentari Santoso; Anis Endang; Indria Indria (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2023)
The purpose of this research is to find out the Management of Communication Privacy on Selebgram at Bengkulu city. This research uses Petronio’s theory, 2002 about communication privacy management. This research uses the qualitative research method. Data are collected by using observation, interview, and documentation as the method. The result of this research generally shows that the informants said it is very important to keep safe the privacy in selebgram era because it helps them for example to keep their figure and prevent from being talked back and can choose or negotiate with self whether to post or not about problems in their lives and family. And only will share good posts to be viewed by the public or followers.